Extração, caracterização e fotorreticulação do colágeno da pele de tilápia visando aplicação em engenharia tecidual - Moraes, Juliana Rafael de (2025)
Collagen, the main structural protein of the extracellular matrix in vertebrates, accounts for over 25% of total human body proteins. Its molecular organization into triple-helical polypeptide chains provides mechanical strength, biochemical stability, and the ability to stimulate cell proliferation. Due to these properties, collagen has strategic applications in biomedical, tissue engineering, food, and pharmaceutical industries. Traditionally sourced from bovine and porcine tissues, its extraction faces sanitary challenges and religious restrictions, driving the search for sustainable alternatives. In this context, aquatic-derived collagen emerges as a promising option, not only due to its abundance and low zoonotic risk but also because it utilizes aquaculture byproducts—which contain 50–70% collagen—adding economic value and reducing import dependency. Acid solubilization is widely employed for extraction as it preserves the protein’s native structure. However, pure collagen exhibits limitations in mechanical properties, requiring modifications such as crosslinking to expand its biomedical use. This study investigated riboflavin (vitamin B₂)-mediated photocrosslinking, a method that uses blue LED light to form hydrogels with poorly explored physicochemical properties. Collagen was extracted from tilapia skin (Oreochromis niloticus) and characterized by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and ¹³C nuclear magnetic resonance (¹³C NMR). Hydrogels were then synthesized with riboflavin (0.1% and 1.0%) and irradiated for 5, 10, 20 and 30 minutes. Thermogravimetric analysis (TGA) revealed higher thermal stability in hydrogels with prolonged crosslinking times, while swelling assays indicated lower water absorption and higher crosslinking density at increased riboflavin concentrations and longer light exposure. The denaturation temperature of crosslinked collagen (45°C) exceeded that of native collagen (37°C), and cytotoxicity tests confirmed its biocompatibility. These results demonstrate that photocrosslinked tilapia-derived collagen exhibits suitable properties for tissue engineering applications, positioning it as a viable and sustainable alternative to conventional collagens.